(untitled) (Global Journal of Human-Social Science, 2021)
Cultural industries have become a significant component of modern economies. There is increasing attention measuring the economic contribution of these industries at national levels, particularly their impact on economic variables. The objective of this study is to illustrate concepts, approaches, methodologies related to cultural economics. Moreover, to shed light on measuring methods of the economic contribution of cultural industries. Using descriptive analysis, we examined the use of these approaches in some selected countries. These countries are; UK, Finland, France, Germany, Italy, and Spain from Europe. Canada and USA from North America. Australia, China and India from the Asia-pacific region. South American economic organization (MERCOSUR) countries for the South American region. South Africa and Egypt from Africa region. The main results revealed the increasing realization of measuring cultural economic contributions in developed countries rather than developing countries. Yet; data limitation is still the main problem of measuring the economic contribution of cultural industries. Furthermore, for international comparison purposes, there is a real need to develop new common concepts and measurements of the economic contribution of cultural industries.